Magnetic Resonance Imaging Findings in Childhood Epilepsy at a Tertiary Hospital in Kenya - Samia, Pauline; Odero, Nicholas; Njoroge, Maureen; Ochieng, Shem; Mavuti, Jacqueline; Waa, Sheila; Gwer, Samson (Frontiers in Neurology, 2021)
Background Neuro-imaging is important for determining etiology and guiding care in early childhood epilepsy. However, access to appropriate imaging in sub-Saharan Africa is modest and as a consequence, aetiological descriptions of childhood epilepsy in the region have been limited. We sought to describe MRI findings in children with epilepsy presenting to a tertiary hospital in Nairobi, Kenya, over a six-year period of routine care. Materials and Methods We undertook a retrospective review of MRI findings of children aged between 0 and 18 years with a diagnosis of epilepsy presenting to the paediatric neurology department of Aga Khan University Hospital in Nairobi, Kenya; between January 2014 and July 2020. Over this period, the hospital had 1.5T MRI machines (GE1.5T Signa Excite and GE 1.5T Signa Explorer) and a 3T MRI machine (Philips 3T Ingenia). MRI images were independently reviewed by two study radiologists and the findings summarized and categorized into a study database. Related clinical and electro-encephalographic (EEG) details were extracted from patient records. Categorical data analysis methods were applied to investigate for relationships between clinically relevant neuro-imaging findings, and key clinical and EEG observations. Results Over the study period, 288 children with a confirmed diagnosis of epilepsy had an MRI. They were of median age of 6 (IQR 2,11) years. Ninety-five (33%) children had abnormal findings on imaging. The most common findings were encephalomalacia related to chronic infarcts (n=18: 6.3%), cerebral atrophy (n=11: 3.8%), disorders of neuronal migration (n=11: 3.8%), periventricular leukomalacia (n=9: 3.1%) and hippocampal sclerosis (n=8: 2.8%). Findings related to infectious aetiology were only observed in four children. Clinical comorbidity and inter-ictal epileptiform activity on EEG were independently associated with abnormal findings on imaging. Conclusion Up to a third of the children who underwent an MRI had a positive yield for abnormal findings. Imaging findings related to infectious aetiologies were little observed in our cohort, in contradistinction to aetiology studies in similar settings. At the time of the study, co-morbidity and inter-ictal epileptiform activity on EEG were associated with abnormal findings on imaging and should be considered in informing prioritization for imaging in childhood epilepsy in this setting.